Bacteroides acidifaciens and its derived extracellular vesicles improve DSS-induced colitis - Zheng, Cihua; Zhong, Yuchun; Xie, Jian; Wang, Zhuoya; Zhang, Wenming; Pi, Yiming; Zhang, Wenjun; Liu, Li; Luo, Jun; Xu, Wei (Frontiers in Microbiology, 2023)
Probiotic therapy" to regulate gut microbiota and intervene in intestinal diseases such as inflammatory bowel disease (IBD) has become a research hotspot. Bacteroides acidifaciens, as a new generation of probiotics, has shown beneficial effects on various diseases. In this study, we utilized a mouse colitis model induced by DSS to investigate how B. acidifaciens positively affects IBD. First, we confirmed that B. acidifaciens has a protective effect on colitis, including alleviating the colitis phenotype, reducing inflammatory response, and improving intestinal barrier function, accom-panied by an increase in the relative abundance of B. acidifaciens and Ruminococcus callidus but a decrease in the relative abundance of Bacteroides fragilis. Further fecal bacterial transplantation or fecal filtrate transplantation confirmed the protective effect of eosinophil-regulated gut microbiota and metabolites on DSS-induced colitis. Finally, we validated that extracellular vesicles (EVs) de-rived from B. acidifaciens contain rich functional proteins that can contribute to the relief of colitis.